Multiple functional targets of the immunoregulatory activity of galectin-1 : Control of immune cell trafficking, dendritic cell physiology, and T-cell fate - Cooper, Dianne (2010)
In the postgenomic era, the study of the glycome- the whole repertoire of saccharides in cells and tissues- has enabled the association of unique glycan structures with specific physiological and pathological processes. The responsability for deciphering this biological information belongs to endogenous glycan-binding proteins or lectins. Galectin-1, a prototype member of a family of structurally-related proteins, has demonstrated selective antiinflammatory and immunoregulatory effects either by controlling immune cell trafficking, fine-tuning dendritic cell physiology and regulating T cell phate. These regulatory functions mediated by an endogenous glycan-binding protein may contribute tuo fullfil the needs for immune cell homeostasis.